Dual-income couple and child care: a look at gender relationships in households - Genta, Natalia (2021)
This article aims to analyze, based on a qualitative study, the limitations, agreements, negotiations and conflicts that dual-income couples in Uruguay face regarding the care of young children. These couples and their interactions are a privileged setting to understand how gender relations are reproduced or problematized at the micro level, in relationships within home when they are faced with care needs. Based on a study focused on child care in three generations of men and women, this article analyzes the ruptures that these couples make concerning the previous ones, but also the inertias they experience in terms of gender mandates and their behaviors.